Blended Learning sebagai Alternatif Model Pembelajaran IPS di Masa Pandemi Covid-19 - Apri Listina Sari; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
Blended learning is a learning model that combines face-to-face and online learning by utilizing a variety of media and technology to support independent learning and provide student learning experiences. The blended learning model is relevant to the learning system during the Covid-19 period, but in Indonesia, especially elementary schools, there are still few that implement it. This study aims to describe the implementation of the blended learning model and its effect on students so that elementary school teachers are interested in implementing the blended learning model in their schools, especially in social studies subject matter. The method used is a systematic literature review through three stages, including collection, reduction, and article review. The results show that the blended learning model can be used as an alternative social studies learning model during the covid-19 pandemic. Blended learning can be applied in elementary schools by offline or hybrid learning using various online platforms.